Persepsi Penyuluh Pertanian Lapangan Terhadap Program Komando Strategi Pertanian (Kostratani) di Kabupaten Lampung Timur - Tanjung, Rahmadani; Rangga, Kordiyana K; Listiana, Indah; Hasanuddin, Tubagus (Fakultas Pertanian, Universitas Lampung, 2023)
Kostratani is the center of agricultural development activities at the sub-district level based on information technology revolution 4.0 to support advanced, modern and independent agricultural development as well as optimizing the duties and functions of BPP in realizing national food sovereignty, so that PPL plays an active role in the success of this program. The purpose of this study was to determine the PPL's perception of the Kostratani program and to determine the factors associated with the PPL's perception of the Kostratani program in East Lampung Regency. This research was conducted in East Lampung Regency. Data collection in this study used the census method, conducted from February to March 2022. The respondents of this study were 24 extension workers in East Lampung Regency. Hypothesis testing using non-parametric statistical test analysis Spearman Rank correlation. The results of the study showed that PPL's perception of the Kostratani program in East Lampung Regency was categorized as good, formal education level, level of knowledge, instructor's ability to information technology, motivation, and government support were significantly related to PPL's perception but age and infrastructure were not significantly related to perception PPL on the Kostratani program.